Antibiotic resistance gene abundances associated with antibiotics and heavy metals in animal manures and agricultural soils adjacent to feedlots in Shanghai; China - Ji, Xiuling; Shen, Qunhui; Liu, Fang; Ma, Jing; Xu, Gang; Wang, Yuanlong; Wu, Minghong (Journal of hazardous materials, 2012)
► Heavy metals were found coexisting with antibiotics in manures and manure-amended agricultural soils. ► The relative abundance of sulfonamide and tetracycline ARGs were high in manures and soils. ► Positive but weak correlations were found between ARGs and their corresponding antibiotics. ► Significant positive correlations were found between some ARGs and typical heavy metals such as Cu, Zn, and Hg. ► Metals able to induce the SOS response may accelerate the dissemination of antibiotic resistance. Eight antibiotic resistance genes (ARGs), 7 heavy metals, and 6 antibiotics were quantified in manures and soils collected from multiple feedlots in Shanghai. The samples were analyzed to determine if ARG abundances were associated with heavy metal concentration and independent of antibiotics. The results revealed the presence of chloramphenicol, sulfonamides and tetracyclines at concentration ranges of 3.27–17.85, 5.85–33.37 and 4.54–24.66mgkg−1, respectively. Typical heavy metals, such as Cu, Zn, and As, were detected at concentration ranges of 32.3–730.1, 75.9–4333.8, and 2.6–617.2mgkg−1. All ARGs tested were detected in the collected samples except tetB(P), which was absent in animal manures. Overall, sulfonamide ARGs were more abundant than tetracycline ARGs. Except for sulII, only a weak positive correlation was found between ARGs and their corresponding antibiotics. On the contrary, significant positive correlations (p<0.05) were found between some ARGs and typical heavy metals. For example, sulA and sulIII were strongly correlated with levels of Cu, Zn and Hg. The data demonstrated that the presence of ARGs was relatively independent of their respective antibiotic inducer. In addition to antibiotics, toxic heavy metals, such as Hg, Cu, and Zn, exerted a strong selection pressure and acted as complementary factors for ARG abundance.